Implementasi Kebijakan Sekolah Bertaraf Internasional - Maryono Maryono (LPPM Press, 2010)
Abstract: government through the National Education Department hasdetermined new policies in the education sectors such as; the act of NationalEducation System(UU Sisdiknas), PP or Government Regulation, Permen orministerial regulation, Kepmen or ministerial decree, policy of pioneering effortof international level school (RSBI), policy of International Level Schools (SBI),immersive schools policy, accelerative schools policy, bilingualism, policy of thechange of education curriculum from year to year, determining the incorporate ofeducation institutions, increasing the quality of SDM ( Peoples resources), and theoperational aid to the education institutions, and so on. All of the efforts have apurpose to increase the national education quality to achieve the nationaleducation aim. The result of the research shows that SBI or International LevelSchool regulation in official of education at Pacitan Regency is only following thepolicy of provide government, and the national government. There is noproponent regulation which is more operational and relevant with the localschools needs.